Peranan Haji Agus Salim dan Semangat Kemerdekaannya Untuk Meningkatkan Rasa Nasionalisme Dikalangan Peserta Didik - Maisarah, Ersya (Program Studi Pendidikan Sejarah, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pattimura, 2023)
The purpose of writing this article is to examine and study the role of national movement leader Haji Agus Salim in Indonesian national history from the time of national revival to independent Indonesia. The national movement is an impact of ethical politics implemented in Indonesia, and the spirit of Indonesian people in gaining independence is a positive thing for this country. One of the most important figures is H. Agus Salim; he made many very meaningful contributions to achieving Indonesian independence. His enthusiasm for resistance was mostly through political channels, such as instilling nilai the value of nationalism to all Indonesian people. His nationalistic spirit should be known and formalized by the students as part of this nation.